2016
DOI: 10.11607/jomi.4468
|View full text |Cite
|
Sign up to set email alerts
|

First-Order Mathematical Correlation Between Damping and Resonance Frequency Evaluating the Bone-Implant Interface

Abstract: In a recent publication, "First-order mathematical correlation between damping and resonance frequency evaluating the bone-implant interface," Kwon et al. [1] found a statistical linear correlation between the Periotest and implant stability quotient values. The Periotest device (Gulden Messtechnik, Bensheim, Germany) evaluates the quality of the bone-implant interface using the damping effect at the interface. When the implant firmly contacts the bone, the damping effect becomes smaller, which reduces the Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…The cells on the Ti implant surfaces seemed to be able to read the configuration of the structural parts of the implant. Considering the fact that implant geometry is a major factor in the initial stability of an implant inserted into bone and that osseointegration contributes to the subsequent stability, such SEM results imply that the initial, or primary, stability is associated with the shape of the crest area and that the secondary, or biological, stability is mainly connected to the cellular behavior at the root area [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The cells on the Ti implant surfaces seemed to be able to read the configuration of the structural parts of the implant. Considering the fact that implant geometry is a major factor in the initial stability of an implant inserted into bone and that osseointegration contributes to the subsequent stability, such SEM results imply that the initial, or primary, stability is associated with the shape of the crest area and that the secondary, or biological, stability is mainly connected to the cellular behavior at the root area [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, a very weak correlation was found between both values during implant placement. [ 12 26 ] However, other studies did report a strong correlation between the same. [ 27 28 ] A recent systematic review concludes that insertion torque and RFA are independent and incomparable methods for measuring primary stability, suggesting that a high insertion torque does not necessarily correspond to a high ISQ value.…”
Section: Discussionmentioning
confidence: 99%